"I Don't Claim to Be the World's Foremost Expert, But . . . ": How Individuals "Know" Family Members Are Not Experiencing Health Issues as Severely as They Claim. (August 2019) - Thompson, Charee M.; Parsloe, Sarah
To understand how individuals come to "know" that their family members are not experiencing their health issues as severely as they claim, we interviewed 32 individuals (nine men and 23 women, M age = 35.28 years, SD = 9.91 years) about a family member who they believe falsifies or exaggerates his or her health condition(s). Our analyses illuminate two interlinked processes of knowledge construction: (a) developing evidentiary standards and (b) gathering evidence. In engaging these processes, participants sought two types of consistency: correspondence with external "facts" (e.g., medical information, cultural [mis]conceptions), and internal coherence (i.e., complaints were highly self-contradictory and unpredictable or were overly predictable). When initial inconsistencies made participants doubt their family member, participants gathered additional evidence, including experiential, behavioral, and interactional evidence, to test and revise their initial suspicions. We discuss the implications of this research for theory and for families coping with illness.